MORPHOLOGICAL STAGES OF THE DEVELOPMENT OF AL-RUTBA CITY - Ibrahim Mowaffaq Hamad; Abdel Nasser Sabry (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The city of Al-Rutba originated and developed like the rest of the cities of Iraq, affected by a number of circumstances and variables that interacted in different ways and led to the emergence of the city in its final form. Especially its geographical location in the middle of the Western Desert, its location made it a commercial station on the trade caravan route and contributed to increasing its commercial activity and providing many job opportunities for the population. Its location also made it characterized by desert cities because of the effects of the environment on its functional and architectural structure, so it grew and developed under the influence of a number of factors that were reflected in its functional and architectural structure that witnessed changes and changes during the stages of growth and development. The research problem was formulated by the following scientific question (What are the most prominent changes that occurred in each stage of the morphological development of the city of AlRutba). In order to answer the question that came in the problem of the research, the hypothesis was formulated according to which: There are a number of factors and variables that contributed to the change in the morphological structure of the city of Al-Rutba, in a way that enables to distinguish several morphological stages. Based on a set of elements that worked in an interactive and integrated manner to draw the urban landscape and the architectural structure of the city, most notably the city plan, its street systems, building materials, architectural style and urban land uses, four morphological stages were distinguished by revealing the changes that occurred in the functional and architectural structure of the city